Competition for Hfq drives kinetic selection of mRNA targets by Escherichia coli small noncoding RNAs - Jorjethe Roca; Yi-Lan Chen; Sarah A. Woodson (Proceedings of the National Academy of Sciences, 2025)
Small noncoding RNAs (sRNAs) regulate gene expression in Escherichia coli bacteria in response to diverse stimuli in the environment and the host. Most sRNAs regulate mRNA expression by directly base pairing with complementary sites in the target mRNA with the help of the chaperone protein Hfq. sRNAs and Hfq must rapidly search hundreds of candidate mRNAs for matched (cognate) targets while discriminating against noncognate targets. Here, we use single-molecule fluorescence microscopy to directly observe how cognate and noncognate mRNAs bind immobilized sRNA–Hfq. The results show that initially unstable sRNA–Hfq–mRNA complexes either dissociate within seconds by ejecting one of the two RNAs, depending on their interactions with Hfq, or are stabilized by sRNA–mRNA base pairing. Cognate mRNAs are more likely to form long-lived sRNA–Hfq–mRNA complexes, even in the presence of competing RNA. Active competition for the mutual Hfq chaperone introduces a kinetic barrier to RNA colocalization that is resolved by base pairing, driving the accumulation of cognate sRNA–mRNA interactions while eliminating noncognate interactions.